Association of Conductive Hearing Loss with the Structural Changes in the Organ of Corti - KAYA, ÖZLEM TUĞÇE; ŞİRVANCI, SERAP (KARGER, 2022)
Objective: The aim of the study was to evaluate the association of conductive hearing loss (CHL) with the structural changes in the organ of Corti. Methods: Twenty ears of 10 healthy adult Wistar albino rats were included in the study. The right ears (n = 10) of the animals served as controls (group 1), and no surgical intervention was performed in these ears. A tympanic membrane perforation without annulus removal was performed under operative microscope on the left ears (n = 5) in 5 of 10 animals (group 2). A tympanic membrane perforation with annulus removal was performed under operative microscope on the left ears (n = 5) of the remaining 5 animals (group 3). Auditory brainstem response testing was performed in the animals before the interventions. After 3 months, the animals were sacrificed, their temporal bones were removed, and inner ears were investigated using scanning electron microscopy (SEM). The organ of Corti was evaluated from the cochlear base to apex in the modiolar axis, and the parameters were scored semiquantitatively. Results: In group 1, the pre- and post-intervention hearing thresholds were similar (p > 0.05). In group 2, a hearing decrease of at least 5 dB was encountered in all test frequencies (p > 0.05). In group 3, at the frequency range of 2-32 kHz, there was a significant hearing loss after 3 months (p < 0.01). After 3 months, the hearing thresholds in group 2 and 3 were higher than group 1 (p < 0.01). The hearing threshold in group 3 was higher than group 2 (p < 0.01). On SEM evaluation, the general cell morphology and stereocilia of the outer hair cells were preserved in all segments of the cochlea in group 1 with a mean SEM score of 0.2. There was segmental degeneration in the general cell morphology and outer hair cells in group 2 with a mean SEM score of 2.2. There was widespread degeneration in the general cell morphology and outer hair cells in group 3 with a mean SEM score of 3.2. The SEM scores of group 2 and 3 were significantly higher than group 1 (p < 0.05). The SEM scores of group 3 were significantly higher than group 2 (p < 0.05). Conclusion: CHL may be associated with an inner ear damage. The severity of damage appears to be associated with severity and duration of CHL. Early correction of CHL is advocated in order to reverse or prevent progression of the inner ear damage, which will enhance the success rates of hearing restoration surgeries. Subjective differences and compliance of the hearing aid users may be due to the impact of CHL on inner ear structures.
Keywords: Hearing loss; Scanning electron microscopy; Organ of Corti; Outer hair cell